DDRs: receptors that mediate adhesion, migration and invasion in breast cancer cells - Emmanuel Reyes-Uribe; Nathalia Serna-Marquez; Eduardo Perez Salazar (AIMS Biophysics, 2015)
Discoidin domain receptors (DDRs) are receptor tyrosine kinases that are activated by native collagens and have an important role during cell adhesion, development, differentiation, proliferation, and migration. DDR deregulation is associated with progression of several different cancers. However, there is limited information about the role of DDRs in the progression of breast cancer. In this review we attempt to collect the most relevant information about DDR signaling and their role in various cancer-related processes such as adhesion, epithelial to mesenchymal transition, migration, invasion, and survival, with a focus on breast cancer.